(untitled) (Revista Contexto & Saúde, 2026)
Background - It is estimated that about 5 to 10% of all breast cancer cases have a hereditary context, in which tumor progression occurs through the activation or repression of important genes in the germ cell line of an individual. BRCA1 is the most penetrant gene associated with breast cancer, and the presence of pathogenic mutations in its sequence increases the risk of developing this neoplasm to 45-75%. In the northern region of Brazil, the largest geographical region of the country, only two studies have been conducted to date to detect allelic variants in this gene. Objectives - This is a transversal study that aimed to assess pathogenic mutations in the BRCA1 gene of breast cancer patients treated in a public health reference unit for cancer research and treatment in the western Amazon. Design, setting and methods- Genetic testing was performed using polymerase chain reaction (PCR) methods and Sanger sequencing of seven important coding regions of the BRCA1 gene. Results - No variants were found in the sequences studied, which may indicate that the frequency of pathogenic mutations in the BRCA1 gene in this population is low. Conclusions - Although no pathogenic mutations were identified in the analyzed sequences, this study provides epidemiological data for a better understanding of the Brazilian mutational profile of genes associated with breast cancer.